Engineered lipase enables selective hydrolysis of palmitic over oleic acyl chains at a two‑phase microfluidic interface - Jin-Zheng Wang; Lu Tan; Cheng-Kun Wu; Xin-Ying Wang; Kheng Lim Goh; Richard Ansah Herman; Shuai You; Sheng Sheng; Fu-An Wu; Jun Wang (Bioresource Technology, 2026)

Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

Reshaping of extracellular polymeric substance scaffolds, microbiota and metabolism mitigates bio-clogging in microbial fuel cell-coupled constructed wetlands - Qinghua Wang; Jiao Yin; Xuewei Fu; Lei Cheng; Xinyue Wu; Xiaofang Li; Haowei Guo; Jun Xiao; Lei Huang (Bioresource Technology, 2026)

Natural-convection-dominated heat transfer from a partially-embedded high-temperature subsea pipeline: Coupled thermo-hydro-soil analysis and scaling law - Jun Cheng; Fu-Ping Gao; Jia-Hao Yu; Xu-Hui Zhang (Ocean Engineering, 2026)

Middle Jurassic isolated dinosaur tracks from Msemrir (Central High Atlas, Morocco): Evidence for theropod occurrence and paleogeographic distribution - Noura Lkebir; Yao-Yan He; Xiong-Wei Zeng; Cheng-Gang Wang; Fa-Fu Wu; Lai-Shi Zhao; Zhi-Jun Niu (Palaeoworld, 2026)

Effects of different drying methods on drying characteristics and quality of chili peppers (Capsicum annuum L.): Insights from changes in carotenoid and alkaloid secondary metabolites - Xuanxuan Yang; Xuefang Li; Fu Cai; Gang Shen; Cheng Zhang; Jun Wang (Food Research International, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Low-cost pillar-ligand engineering toward ultramicroporous MOFs for efficient SF6/N2 separation - Biao Fu; Hui-Ting Zheng; Rui-Ming Li; Duo Yue; Liang Song; Zhang-Wen Wei; Robert Langer; Mihail Barboiu; Ji-Jun Jiang; Cheng-Yong Su (Chemical Engineering Journal, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Annual energy use and economic performance of rice-based cropping systems: A three-year field study in Southwest China - Chuanhai Shu; Qingyue Cheng; Binbin Liu; Hongkun Xie; Yuanqing Shi; Mingming Hu; Hao Fu; Peng Ma; Na Li; Zhonglin Wang; Zongkui Chen; Yongjian Sun; et al. (Journal of Cleaner Production, 2026)

Preferentially selective lithium recovery from spent lithium-ion battery leachates using NaBPh4/TBP synergistic extraction - Qian Cheng; Yue Wang; Yongxiang Wang; Panfeng Gao; Jun-Tao Li; Jiangxue Long; Haiyan Fu (Hydrometallurgy, 2026)

Mechanism Analysis and Precise Regulation Strategies of Non-Thermal Effects and Synergistic Effects in Microwave Disinfection - Ying-Xiang Fu; Jun-Jie Wang; Hao Wu; Zhi-Cheng Pan; Wei Hu; Ye Du (Current Pollution Reports, 2026)

Novel eudesmanolides from the flowers of Pentanema britannicum (L.) D.Gut.Larr with antidepressant activities - Yu-Qing Xie; Xin-Yue Zhang; Jun-Hui Zhang; Ping He; Sheng-He Yang; Yan Fu; Zhi-Yu Ni; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Enhanced mechanical, thermal, and rheological properties of nanocellulose-reinforced multifunctional sanxan gum hydrogels - Yue Wang; Baoping Wang; Ping Cheng; Xue Zhang; Jun Han; Fang Tian; Lina Fu; Zhiping Fan (Food and Bioproducts Processing, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Mg–K isotopic compositions deciphering mantle heterogeneity beneath southeast Tibet - Qiong Chen; Hao Cheng; Guo-Chun Zhao; Mei-Fu Zhou; Ping-Ping Liu; Wen-Jun Li; Min Sun (Geochimica et Cosmochimica Acta, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Synergistic inhibition of advanced glycation end products and enhancement of flavor by the combination of oligomeric proanthocyanidins and glycated yeast proteins - Jing-jing Fu; Bo-wen Ru; Qi-cheng Zhang; Yu-jun Wu; Hai-yang Feng; Lian-ping Zheng; Yue-wen Chen (Food Research International, 2026)

New sesquiterpenoids from the flowers of Pentanema britannicum with cytotoxicity activities - Jun-Hui Zhang; Ping He; Sheng-He Yang; Jia-Li Lang; Yan Fu; Jian Su; Yu-Cheng Gu; Yi-Bing Wu (Natural Product Research, 2026)

Green upcycling of tigogenin from sisal waste: Chemoenzymatic cascade synthesis of progesterone derivatives as an alternative to traditional steroid production processes - Lu Song; Zhi-Kun Luo; Fu-Cheng He; Lan-Ya Huang; Liang-Bin Xiong; Yong-Jun Liu; Dong-Zhi Wei; Feng-Qing Wang (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Computer vision-assisted sorting and selective cultivation of high-activity anammox granules - Shi-Jun Li; Haoran Li; Hui-Min Fu; Yi-Cheng Wang; Xun Weng; Wei Wang; You-Peng Chen (Water Research, 2026)

Experimental study on monitoring model of bearing capacity characteristics of uplift piles based on flexible piezoelectric sensing - Jun Wang; Xinzhe Tang; Zhiming Liu; Cheng Zhang; Junfeng Ni; Ziyang Gao; Hongtao Fu; Xueyu Geng; Chaoyue Wu (Transportation Geotechnics, 2026)

Hybridization and incomplete lineage sorting characterize the evolutionary history of two East Asian clades of Stewartia (Theaceae) - Han-Yang Lin; Miao Sun; Jian-Jun Jin; Cheng-Xin Fu; Douglas E. Soltis; Pamela S. Soltis; Yun-Peng Zhao (Molecular Phylogenetics and Evolution, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Insights into the enhanced flux and robust desalination of hydrogel composite Janus membrane in membrane distillation: overlooked interfacial compatibility - Shu Jiang; Anqi Luo; Shilei Fu; Yanrui Wang; Kexin Hou; Jun Ma; Longfeng Hu; Nuo Cheng; Xiaobin Tang; Heng Liang (Chemical Engineering Journal, 2026)

The Bujinhei Pb-Zn deposit in the southern Great Xing'an Range, China: An example of the reduced hydrothermal vein type Pb-Zn mineralization system - Cheng-yang Wang; Yun-sheng Ren; Yi-cun Wang; Zhen-jun Sun; Li-juan Fu (Journal of Geochemical Exploration, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Characterisation of cytochrome c oxidase-coding genes from mung bean and their response to cadmium stress based on genome-wide identification and transcriptome analysis - Yan Leng; Zhuan-Bin Niu; Shao-Hua Liu; Fu-Jun Qiao; Gui-Fang Liu; Bin Cheng; Shi-Weng Li (Molecular Biology Reports, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Development of a Private Cloud Platform for Distributed Logging Big Data and Its Application to Geo-Engineering Evaluation of Geothermal Fields - Xi Cheng; Hai-cheng Fu; Jun He (Applied Geophysics, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Optimizing rotation lengths of major plantation species for improved wood production in southern China - Minyu Dou; Zhen Wang; Tingshuo Zhang; Zhixin Cheng; Jun Zhang; Wenzheng Fu; Markku Larjavaara; Wennong Kuang; Demeng Jiang; Fangyuan Hua (Forest Ecology and Management, 2025)

Development of iterative genome-editing method based on a Rock-Paper-Scissors strategy in Clostridium tyrobutyricum for butyl butyrate from lignocellulosic biomass hydrolysate - Fating Ye; Jun Feng; Xiaolong Guo; Jiale Cheng; Hongxin Fu; Jufang Wang (Chemical Engineering Journal, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Inserting sodium lignosulfonate into multilayer graphene in boosting the interfacial polarization of triboelectric nanogenerators for monitoring the impact state of fruits - Meiyi Chen; Xin Li; Tianshuang Bao; Cheng Cai; Yehan Tao; Jie Lu; Chenglong Fu; Jinwen Hu; Jun Xie; Xiaodong Xia; Xuejiao Wang; Jian Du; et al. (Chemical Engineering Journal, 2025)

The critical role of OsYTH10 in promoting early flowering of rice under long sunlight - Jun Yang; Zhihao Chen; Peng Wang; Mvuyeni Nyasulu; Qin Cheng; Xiaopeng He; Jie Xu; Junru Fu; Dahu Zhou; Linjuan Ouyang; Haohua He; Jianmin Bian (Theoretical and Applied Genetics, 2025)

Regional airflow velocity control to meet the diverse requirements of unevenly distributed maize threshing mixtures - Meng Zhang; Chao Cheng; Jun Fu; Zhi Chen; Luquan Ren (Biosystems Engineering, 2025)

Scaling of urban residential building stock system and carbon emissions accounting for vacant houses in China - Wanru Leng; Guangxin Liu; Xiaoyu Cheng; Yang Li; Shoujuan Tang; Jun Ning; Yuanhang Li; Hang Fu; Lei Shi (Resources, Conservation and Recycling, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Intelligent Alignment Control for Floating Raft Air Spring Mounting System Under Coupled Hull–Raft Deformation - Jian-Wei Cheng; Wen-Jun Bu; Ze-Chao Hu; Jun-Qiang Fu; Hong-Rui Zhang; Liang Shi (Journal of Marine Science and Engineering, 2025)
Shaft alignment is adversely affected by the increasingly severe coupled hull–raft deformation in deep-diving, highly integrated submersibles, thereby compromising operational safety and potentially amplifying vibration noise. To address to this issue, this paper investigates an intelligent alignment control method for the floating raft air spring mounting system (ASMS) applied to marine propulsion unit (MPU) under coupled hull–raft deformation conditions. A multi-objective alignment control algorithm was developed based on the NSGA-II optimization method within an N-step receding horizon optimal control framework, enabling simultaneous achievement of shaft alignment attitude adjustment, hull deformation compensation, raft deformation suppression, and pneumatic energy consumption. Experimental validation was conducted on two distinct ASMS prototypes to evaluate the control algorithm. Tests performed on the ASMS for MPU (MPU-ASMS) prototype demonstrated effective compensation of hull-induced deformations, maintaining shaft alignment offsets within ±0.3 mm and angularities within ±0.5 mm/m. Concurrently, experiments on the floating raft ASMS for the stern compartment (SC-FR-ASMS) achieved precise control of axial offsets within ±0.3 mm, angularities within ±0.5 mm/m, and vertical displacements of critical monitoring points within ±1 mm. The adaptive control strategy additionally proved effective in suppressing raft deformation while simultaneously optimizing pneumatic energy consumption. This research provides robust theoretical and technical foundations for intelligent vibration isolation systems in deep-sea equipment to accommodate extreme-depth-induced hull deformation and large-scale raft deformation.

Coupling effect of phytic acid and chlorite on uranium removal by Shewanella putrefaciens under simulated natural environment - Qingrong Li; Yang-Yang Zhang; Guo-Hao Zhang; Yilin Qin; Wencai Cheng; Xinyu Wang; Liuyuan Fu; Nan Wang; Xiaoan Li; Faqin Dong; Jun Li; Xiaoqin Nie (Water Research, 2025)

Long-term settlement of deepsea pipelines on a soft clayey seabed: Poro-elasto-viscoplastic modeling - Jun Cheng; Jian Li; Fu-Ping Gao; Zhen-Yu Yin (Ocean Engineering, 2025)

Unsupervised SAR image change detection using multi-level graph attribute matching - Jun Wang; Qiongjun Fu; Jiahui Li; Sanku Niu; Yaohui Zhu; Yuechao Zhang; Pengle Cheng (International Journal of Remote Sensing, 2025)

New thiohydantoin derivatives from the roots of Lepidium meyenii - Wen-Xin Liu; Jun Li; Cheng-Juan Liao; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2025)

New Colorimetric Chemosensor for Rapid Naked-Eye Detection of Cu2+ and Its Application in Gas-Generating Agents - Xiaohong Cheng; Jun You; Shaoyong Meng; Wenjie Shen; Tao Du; Wenbin Fu; Yunqiang Luo; Song Wang (Journal of Fluorescence, 2025)

3D printing of synthetic microbial consortium for boosting bioelectricity generation from starch - Xiao-Jing Wang; Jie Wang; Zhizhi Yang; Ye Zhang; Kai Cheng; Jun-Ying Han; Fu-Xiang Chang; Yang-Chun Yong (Chemical Engineering Journal, 2025)

Mechanism study of the effect of a surface liquid film on the collision adhesion behaviour of rice stalks - Jun Fu; Meng Zhang; Chao Cheng; Haiming Zhao; Luquan Ren (Biosystems Engineering, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

In-situ packing self-intumescent aerogel particles in rigid polyurethane foam towards thermal insulation, flame retardance and smoke suppression - Ning Yu; Ting Wang; Cheng-Xu Xu; Xue Gou; Ying-Jiao Zhan; Wenli An; Zhi-Cheng Fu; Jinni Deng; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Thickness monitoring of threshing mixture on the oscillating plate of corn grain harvester - Jun Fu; Meng Zhang; Chao Cheng; Haiming Zhao; Luquan Ren (Computers and Electronics in Agriculture, 2024)

N6-methyladenosine demethylase FTO regulates neuronal oxidative stress via YTHDC1-ATF3 axis in arsenic-induced cognitive dysfunction - Lixiao Zhou; Renjie Li; Fu Wang; Ruiqi Zhou; Yinyin Xia; Xuejun Jiang; Shuqun Cheng; Fanghong Wang; Danyang Li; Jun Zhang; Lejiao Mao; Xuemei Cai; et al. (Journal of Hazardous Materials, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

A semi-empirical parameter predicting the sensitivity of energetic materials from external pressure - Zhi-Xin Bai; Wei Zeng; Cheng-Lu Jiang; Fu-Sheng Liu; Zheng-Tang Liu; Qi-Jun Liu (Chemical Engineering Journal, 2024)

Corrigendum to “Lubricating MXenzyme-based hybrid hydrogel reverses oxidative damage to alleviate osteoarthritis” [Chem. Eng. J. 482 (2024) 148815] - Zhao Zhang; Debin Cheng; Jingxin Pan; Dong Liu; Jun Fu; Hongbin Fan (Chemical Engineering Journal, 2024)

Microplastics weaken the digestion and absorption functions in the golden pompano (Trachinotus blochii) by affecting the intestinal structure, bacteria and metabolites - Fu Cheng Yao; Chun Xiu Jin; Huan Liang; Yu Zhang; Yue Gu; Fei Biao Song; Zhi Zhou; Jun Long Sun; Jian Luo (Chemosphere, 2024)

Expression of genes related to gonadal development and construction of gonadal DNA methylation maps of Trachinotus blochii under hypoxia - Yue Gu; Chun Xiu Jin; Zai Hui Tong; Tian Jiang; Fu Cheng Yao; Yu Zhang; Jie Huang; Fei Biao Song; Jun Long Sun; Jian Luo (Science of The Total Environment, 2024)

Recent advances in preferentially selective Li recovery from spent lithium-ion batteries: A review - Qian Cheng; Ze Wang; Yue Wang; Jun-Tao Li; Haiyan Fu (Journal of Environmental Chemical Engineering, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Efficient production of butyl butyrate from mannitol by engineered Clostridium tyrobutyricum - Xiaolong Guo; Fating Ye; Chenchen Nan; Jiale Cheng; Jun Feng; Hongxin Fu; Jufang Wang (Chemical Engineering Journal, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Integration of bulk-surface charge polarization and active site manipulation for highly efficient photocatalytic aerobic oxidation of sulfides - Jun Wan; Yang-Ai Ma; Yina Nie; Junhao Cheng; Chengming Wang; Lin Liu; Feng Fu (Chemical Engineering Journal, 2024)

Correction to: Statistical investigation of induced seismicity associated with the impoundment of the Xiangjiaba Reservoir, Southwestern China - Ziguo Fu; Fei Chen; Jianhui Deng; Siyuan Zhao; Hua Li; Shigui Dai; Yuping Shao; Ying Fu; Jun Zhu; Wanzheng Cheng (Bulletin of Engineering Geology and the Environment, 2024)

Statistical investigation of induced seismicity associated with the impoundment of the Xiangjiaba Reservoir, Southwestern China - Ziguo Fu; Fei Chen; Jianhui Deng; Siyuan Zhao; Hua Li; Shigui Dai; Yuping Shao; Ying Fu; Jun Zhu; Wanzheng Cheng (Bulletin of Engineering Geology and the Environment, 2024)

Micro formation mechanism of oil–water inversion in reservoirs based on water film theory—An example from the Dawangzhuang Oilfield in Bohai Bay Basin - Xiao Hu; Longchuan Pu; Aihua Ran; Jun Xie; Fengqun Li; Yuzong Cheng; Suhua Zhang; Zhe Li; Qiongyao Pu; Jialin Fu (Fuel, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Lubricating MXenzyme-based hybrid hydrogel reverses oxidative damage to alleviate osteoarthritis - Zhao Zhang; Debin Cheng; Jingxin Pan; Dong Liu; Jun Fu; Hongbin Fan (Chemical Engineering Journal, 2024)

MiRNAs enabled Golden pompano (Trachinotus blochii) in response to different reoxygenation patterns after hypoxic stress - Tian Jiang; Jun Long Sun; Chun Xiu Jin; Yu Zhang; Zai Hui Tong; Yue Gu; Fu Cheng Yao; Li Ping Shi; Fei Biao Song; Jian Luo (Aquaculture, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Strategies for fertilizer management to achieve higher yields and environmental and fertilizer benefits of rice production in China - Zongkui Chen; Xinrui Li; Tao Liu; Hao Fu; Xiaojuan Yuan; Qingyue Cheng; Qin Liao; Yue Zhang; Weitao Li; Yongjian Sun; Zhiyuan Yang; Jun Ma; et al. (Science of The Total Environment, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Photocatalytic degradation of bisphenol A by temperature-sensitive magnetic hydrogel with enhanced service life - Wenhui Chen; Wei Mao; Zhiqiang Liu; Weilin Hou; Naresh Kumar; Jun Sun; Xingwei Cai; Cheng Huang; Wei Shen; Fu Yang; Yanjuan Cui; Hian Kee Lee; et al. (Journal of Hazardous Materials, 2023)

A pan-coronavirus peptide inhibitor prevents SARS-CoV-2 infection in mice by intranasal delivery - Lili Wu; Anqi Zheng; Yangming Tang; Yan Chai; Jiantao Chen; Lin Cheng; Yu Hu; Jing Qu; Wenwen Lei; William Jun Liu; Guizhen Wu; Shaogui Zeng; et al. (Science China Life Sciences, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Local provincialism of late Permian plant–arthropod associations in South Cathaysia: Evidence of arthropod-mediated damages in a Wuchiapingian assemblage of South China - Fu-Jun Ma; Die-Die Luo; Song Liu; Cheng-Wan Zhang; Qiu-Jun Wang; Bing-Xia Li; Chuan-Yuan Liu; Bai-Nian Sun; Xiao He (Journal of Asian Earth Sciences, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Radon adsorption and air purification by Spanish moss (Tillandsia usneoides) and its metabolic response to radon exposure - Qian Fu; Jun-cheng Liang; Jin-long Lai; Xue-gang Luo (Environmental Pollution, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

Gastrointestinal digestion fates of lipids based on pH-stat and Caco-2 cells models: Superior bioavailability of triglyceride monomer derived from silkworm pupae oil - Cheng-Hai Yan; Xiao-Meng Xun; Richard A. Herman; Yu-Fan Zhan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Bioscience, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

One positive part of copper ion on biocatalysts: CNPs@Cu-Trypsin-assisted aqueous extraction technique for simultaneous exploration of edible insect oil and protein - Jin-Zheng Wang; Cheng-Kun Wu; Xin-Ying Wang; Yuan-Zhi Xu; Richard Ansah Herman; Sheng Sheng; Shuai You; Jun Wang; Fu-An Wu (Chemical Engineering Journal, 2023)

Different reoxygenation rates induce different metabolic, apoptotic and immune responses in Golden Pompano (Trachinotus blochii) after hypoxic stress - Tian Jiang; Ye Song Liang; Yue Gu; Fu Cheng Yao; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Jun Long Sun; Jian Luo (Fish & Shellfish Immunology, 2023)

Vsig4+ resident single-Kupffer cells improve hepatic inflammation and fibrosis in NASH - Hui-Yi Li; Seng-Wang Fu; Jun-Cheng Wu; Zheng-Hong Li; Ming-Yi Xu (Inflammation Research, 2023)

Effects of organic carbon sources on algal biofilm formation and insight into mechanism - Jun Qian; Siyi Fu; Jingjing Li; Tatsuki Toda; Hongwu Li; Mutsumi Sekine; Yoshiki Takayama; Shinichi Koga; Shengxi Shao; Liangliang Fan; Peilun Xu; Xiru Zhang; et al. (Algal Research, 2023)

Evidence of aircraft activity impact on local air quality: A study in the context of uncommon airport operation - Hao Xu; Kai Xiao; Jun Pan; Qingyan Fu; Xiaodong Wei; Junrui Zhou; Yamei Yu; Xue Hu; Huarui Ren; Jinping Cheng; Shitao Peng; Ningning Hong; et al. (Journal of Environmental Sciences, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Combined population transcriptomic and genomic analysis reveals cis-regulatory differentiation of non-coding RNAs in maize - Jiawen Lu; Sihan Zhen; Jie Zhang; Yuxin Xie; Cheng He; Xiaoli Wang; Zheyuan Wang; Song Zhang; Yongxiang Li; Yu Cui; Guoying Wang; Jianhua Wang; et al. (Theoretical and Applied Genetics, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Four sesquiterpenoids from the vegetable raw material Schisandra chinensis (Turcz.) Baill.: leaves and stems - Yong-Cheng Yang; Lu-Qi Liu; Kun-Jun Wang; Xue-Qing Zhang; San-Peng Fan; Xiao-Xu Gao; An-Hua Wang; Jing-Ming Jia; Chun-Wang Fu (Natural Product Research, 2022)

Alteromonas oceanisediminis sp. nov., isolated from deep-sea sediment - Xiao-Yu Zhang; Zhen Wang; Jun-Hui Cheng; Hui-Hui Fu; Yu-Zhong Zhang; Xiu-Lan Chen; Xi-Ying Zhang; Xiao-Yan Song; Yu-Qiang Zhang; Fei Xu (Archives of Microbiology, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Talaromyces Marneffei Infection in an HIV-Negative Child with a CARD9 Mutation in China: A Case Report and Review of the Literature - Cheng-yan You; Fang Hu; Si-wei Lu; Dan-dan Pi; Feng Xu; Cheng-jun Liu; Yue-qiang Fu (Mycopathologia, 2021)

Temperature-induced changes in the proteome of Pseudomonas aeruginosa during petroleum hydrocarbon degradation - Jun-Di Wang; Cheng-Tun Qu; Shao-Fu Song (Archives of Microbiology, 2021)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Genome optimization for improvement of maize breeding - Shuqin Jiang; Qian Cheng; Jun Yan; Ran Fu; Xiangfeng Wang (Theoretical and Applied Genetics, 2020)

GPS satellite inter-frequency clock bias estimation using triple-frequency raw observations - Lei Fan; Chuang Shi; Min Li; Cheng Wang; Fu Zheng; Guifei Jing; Jun Zhang (Journal of Geodesy, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Evaluating three satellite-based precipitation products of different spatial resolutions in Shanghai based on upscaling of rain gauge - Weiyue Li; Xiaogang He; Weiwei Sun; Marco Scaioni; Dongjing Yao; Jing Fu; Yu Chen; Bin Liu; Jun Gao; Xin Li; Guodong Cheng (International Journal of Remote Sensing, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

The niches of nuthatches affect their lineage evolution differently across latitude - Yu‐Chi Chen; Masoud Nazarizadeh; Fu‐Min Lei; Xiao‐Jun Yang; Cheng‐Te Yao; Feng Dong; Lu Dong; Fa‐Sheng Zou; Sergei V. Drovetski; Yang Liu; Chun‐Cheng Huang; Chih‐Ming Hung (Molecular Ecology, 2019)
Ecological niche evolution can promote or hinder the differentiation of taxa and determine their distribution. Niche‐mediated evolution may differ among climatic regimes, and thus, species that occur across a wide latitudinal range offer a chance to test these heterogeneous evolutionary processes. In this study, we examine (a) how many lineages have evolved across the continent‐wide range of the Eurasian nuthatch ( Sitta europaea ), (b) whether the lineages’ niches are significantly divergent or conserved and (c) how their niche evolution explains their geographic distribution. Phylogenetic reconstruction and ecological niche models (ENMs) showed that the Eurasian nuthatch contained six parapatric lineages that diverged within 2 Myr and did not share identical climatic niches. However, the niche discrepancy between these distinct lineages was relatively conserved compared with the environmental differences between their ranges and thus was unlikely to drive lineage divergence. The ENMs of southern lineages tended to cross‐predict with their neighbouring lineages whereas those of northern lineages generally matched with their abutting ranges. The coalescence‐based analyses revealed more stable populations for the southern lineages than the northern ones during the last glaciation cycle. In contrast to the overlapping ENMs, the smaller parapatric distribution suggests that the southern lineages might have experienced competitive exclusion to prevent them from becoming sympatric. On the other hand, the northern lineages have expanded their ranges and their current abutting distribution might have resulted from lineages adapting to different climatic conditions in allopatry. This study suggests that niche evolution may affect lineage distribution in different ways across latitude.

Evaluation genotypes of cancer cell lines HCC1954 and SiHa by short tandem repeat (STR) analysis and DNA sequencing - Jiewen Fu; Jingliang Cheng; Xiaoyan Liu; Jun Li; Chunli Wei; Xiaoli Zheng; Tao He; Junjiang Fu (Molecular Biology Reports, 2018)

Biological and chemical compositions of atmospheric particulate matter during hazardous haze days in Beijing - Zhendong Guo; Zhongyi Wang; Lu’an Qian; Zongzheng Zhao; Chunmao Zhang; Yingying Fu; Jiaming Li; Cheng Zhang; Bing Lu; Jun Qian (Environmental Science and Pollution Research, 2018)

Structural characterisation of a water-soluble polysaccharide from tissue-cultured Dendrobium huoshanense C.Z. Tang et S.J. Cheng - Hua-Yang Si; Nai-Fu Chen; Nai-Dong Chen; Cheng Huang; Jun Li; Hui Wang (Natural Product Research, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Characterization and speciation of mercury in mosses and lichens from the high-altitude Tibetan Plateau - Jun-juan Shao; Cheng-bin Liu; Qing-hua Zhang; Jian-jie Fu; Rui-qiang Yang; Jian-bo Shi; Yong Cai; Gui-bin Jiang (Environmental Geochemistry and Health, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Evaluation of the land carrying capacity of major grain-producing areas and the identification of risk factors - Kun Cheng; Qiang Fu; Song Cui; Tian-xiao Li; Wei Pei; Dong Liu; Jun Meng (Natural Hazards, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

The Regulatory Roles of ncRNA Rli60 in Adaptability of Listeria monocytogenes to Environmental Stress and Biofilm Formation - Ye-long Peng; Qing-ling Meng; Jun Qiao; Kun Xie; Cheng Chen; Tian-li Liu; Zheng-xiang Hu; Yu Ma; Xue-peng Cai; Chuang-fu Chen (Current Microbiology, 2016)

Reflux characteristics of 113 GERD patients with abnormal 24-h multichannel intraluminal impedance-pH tests - Yuan-yuan Nian; Cheng Feng; Fu-chun Jing; Xue-qin Wang; Jun Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

mTOR ATP-competitive inhibitor INK128 inhibits neuroblastoma growth via blocking mTORC signaling - Huiyuan Zhang; Jun Dou; Yang Yu; Yanling Zhao; Yihui Fan; Jin Cheng; Xin Xu; Wei Liu; Shan Guan; Zhenghu Chen; Yan shi; Roma Patel; et al. (Apoptosis, 2015)

The Clinical Study of the Optimalization of Surgical Treatment and the Traditional Chinese Medicine Intervention on Palmar Hyperhidrosis - Yong Yang; Zhikun Yan; Xiaoqing Fu; Liwen Dong; Linhai Xu; Jun Wang; Genmiao Cheng (Cell Biochemistry and Biophysics, 2014)

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

The Impact of Microbial Immune Enteral Nutrition on the Patients with Acute Radiation Enteritis in Bowel Function and Immune Status - Feng shao; Fu-ze Xin; Cheng-gang Yang; Dao-gui Yang; Yue-tang Mi; Jun-xiu Yu; Guo-yong Li (Cell Biochemistry and Biophysics, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Activation of mammalian target of rapamycin contributes to pain nociception induced in rats by BmK I, a sodium channel-specific modulator - Feng Jiang; Li-Ming Hua; Yun-Lu Jiao; Pin Ye; Jin Fu; Zhi-Jun Cheng; Gang Ding; Yong-Hua Ji (Neuroscience Bulletin, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Association of glutathione S-transferase P1 gene polymorphism with the histological types of lung cancer: a meta-analysis - Xu Feng; Hua-Fu Zhou; Bao-Shi Zheng; Jun-Jie Shi; Cheng Luo; Jia-Jin Qin (Molecular Biology Reports, 2013)

Development and identification of a wheat-Leymus mollis multiple alien substitution line - Ji-Xin Zhao; Wan-Li Du; Jun Wu; Xue-Ni Cheng; Yang Gao; Yu-Hui Pang; Xin-Hong Chen; Shu-Hui Liu; Qun-Hui Yang; Jie Fu (Euphytica, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Optimization of fermentation process for the production of intracellular polysaccharide from Paecilomyces cicadae and the immuno-stimulating activity of intracellular polysaccharide - Jun-Wen Cheng; Yan-Bin Wang; Liang He; Hua Qian; Li-Zhong Fu; Hai-Bo Li (World Journal of Microbiology and Biotechnology, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

A novel lignan glycoside with antioxidant activity from Tinospora sagittata var. yunnanensis - Xiang-Zhong Huang; Chun-Mei Cheng; Yun Dai; Guang-Miao Fu; Jun-Ming Guo; Hui Liang; Chao Wang (Natural Product Research, 2012)

Comparative full-length sequence analysis of Marek’s disease virus vaccine strain 814 - Feng Zhang; Chang-Jun Liu; Yan-Ping Zhang; Zhi-Jie Li; Ai-Ling Liu; Fu-Hai Yan; Feng Cong; Yun Cheng (Archives of Virology, 2012)

Fas/FasL pathway-mediated alveolar macrophage apoptosis involved in human silicosis - San-qiao Yao; Liying Wang Rojanasakul; Zhi-yuan Chen; Ying-jun Xu; Yu-ping Bai; Gang Chen; Xi-ying Zhang; Chun-min Zhang; Yan-qin Yu; Fu-hai Shen; Ju-xiang Yuan; Jie Chen; et al. (Apoptosis, 2011)

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.) - Xiao-dong Chen; Dong-fa Sun; De-fu Rong; Jun-hua Peng; Cheng-dao Li (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

A double-blind, placebo-controlled study of traditional Chinese medicine sarsasapogenin added to risperidone in patients with negative symptoms dominated schizophrenia - Shi-Fu Xiao; Hai-Bo Xue; Xia Li; Chao Chen; Guan-Jun Li; Cheng-Mei Yuan; Ming-Yuan Zhang (Neuroscience Bulletin, 2011)

Induction of lactadherin mediates the apoptosis of endothelial cells in response to advanced glycation end products and protective effects of grape seed procyanidin B2 and resveratrol - Bao-ying Li; Xiao-li Li; Qian Cai; Hai-qing Gao; Mei Cheng; Jian-hua Zhang; Jun-fu Wang; Fei Yu; Rui-hai Zhou (Apoptosis, 2011)

Up-regulation of growth factor independence 1 in endotoxin tolerant macrophages with low secretion of TNF-α and IL-6 - Min-Fang Zhu; Jing Zhang; Jie-Ming Qu; Hui-Jun Zhang; Shuang-Cheng Zhou; Sheng-Fu Dong; Hong-Ni Jiang; Hanssa Summah (Inflammation Research, 2010)

2-(3,5-Dibromo-4-hydroxyphenyl)imidazo[4,5-f][1,10]phenanthrolinoruthenium(II) complexes: synthesis, characterization, cytotoxicity, apoptosis, DNA-binding and antioxidant activity - Yun-Jun Liu; Zhen-Hua Liang; Zheng-Zheng Li; Cheng-Hui Zeng; Jun-Hua Yao; Hong-Liang Huang; Fu-Hai Wu (BioMetals, 2010)

First-principle conformational analysis of glycine residues in the αβ-tubulin dimer - Gang Yang; Cheng Xing; Cheng-Bu Liu; Yu-Jie Fu; Li-Jun Zhou; Yuan-Gang Zu (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Trade-offs between constitutive and induced resistance in wild crucifers shown by a natural, but not an artificial, elicitor - Peng-Jun Zhang; Jin-Ping Shu; Cheng-Xin Fu; Yun Zhou; Ying Hu; Myron P. Zalucki; Shu-Sheng Liu (Oecologia, 2008)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)